Assessment of chemical disinfectants efficacy against Escherichia coli biofilm developed on glass and wood at refrigeration and room temperatures - Nor Iza, A.Rahman; Anas, Muazu; Umar Faruk, Abdullahi (Open Science Publishers LLP Inc., 2015)
Objectives: The aim of this work was to study the formation of biofilm on glass and wood coupons at refrigeration and room temperatures, different incubation periods and to assess the efficacy of hydrogen peroxide (HP), Para Acetic Acid (PAA), Sodium hypochlorite (SH) and mixture of PAA + SH against the biofilm.